The Politics of Authenticity in a National Heritage Site in Israel - Noy, Chaim (Qualitative Sociology Review, 2009)
This paper offers a multifaceted appreciation of the political roles played by authenticity in modern tourism. The study, located at a national heritage and commemoration site in Jerusalem, Israel, traces authentic occurrences—manifestations and representations—that culminate in an ideological ecology of authenticity. Through this depiction, the active and often veiled role authenticity, understood as a social structure, plays is foregrounded. A special place within this ecology is reserved for the role performed by the site’s visitor book. The paper conceptualizes the commemorative visitor book as an ideological and institutional interface, which serves as an authenticating device. This device allows a transformation of visitors unto ideological social agents who partake in the structure of national commemoration in Israel.